2020
DOI: 10.21315/tlsr2020.31.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Geoaccumulation Index and Enrichment Factor of Arsenic in Surface Sediment of Bukit Merah Reservoir, Malaysia

Abstract: An investigation study was conducted in Bukit Merah Reservoir (BMR) for the assessment of arsenic concentration in the surface sediment in 23 sampling stations. The sediment samples were digested and analysed for arsenic using Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Sediment parameters such as pH (4.42 ± 0.71), redox potential (121.77 ± 42.45 mV), conductivity (205.7 ± 64.07 μS cm–1) and organic matter (25.35 ± 9.34%) were also examined. The main objectives of this study are to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Some authors have observed that using reference environments to calculate the IGEO results in higher values when compared with those calculated considering CS as background (Ghrefat et al, 2011;Kasemodel et al, 2019;Lange, 2018). Discrepancies between IGEO and EF have also reported, and often associated with the choice of reference element, resulting in over-or underestimated of EF values (Abdullah et al, 2020;Shafie et al, 2007). In the present study, the indexes calculated using CS as a reference indicate higher contamination for some metals.…”
Section: Pollution Indexmentioning
confidence: 41%
“…Some authors have observed that using reference environments to calculate the IGEO results in higher values when compared with those calculated considering CS as background (Ghrefat et al, 2011;Kasemodel et al, 2019;Lange, 2018). Discrepancies between IGEO and EF have also reported, and often associated with the choice of reference element, resulting in over-or underestimated of EF values (Abdullah et al, 2020;Shafie et al, 2007). In the present study, the indexes calculated using CS as a reference indicate higher contamination for some metals.…”
Section: Pollution Indexmentioning
confidence: 41%
“…The referenced metals are Mn, Sc, Al, Fe, and Sn. In this study, we used Fe as a reference metal due to its relatively high levels in the earth’s crust [ 51 , 59 , 62 , 63 , 64 ]. where [X/M ref ] sample and [X/M ref ] crust refer to the ratio of mean concentrations (mg/kg) of the target metal(oid) in the examined soil and continental crust, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The geo-accumulation index, conceived by the esteemed German scientist G. Müller, serves as a metric to quantify the degree of accumulation of heavy metals or other pollutants within soil matrices [39,40]. In contrast to alternative methodologies for assessing pollution, the geo-accumulation index method stands as distinct because of its inclusion of factors influencing shifts in baseline values due to natural diagenesis.…”
Section: Geo-accumulation Indexmentioning
confidence: 99%